2013
DOI: 10.1371/journal.pone.0063607
|View full text |Cite
|
Sign up to set email alerts
|

Senescent Fibroblasts Enhance Early Skin Carcinogenic Events via a Paracrine MMP-PAR-1 Axis

Abstract: The incidence of carcinoma increases greatly with aging, but the cellular and molecular mechanisms underlying this correlation are only partly known. It is established that senescent fibroblasts promote the malignant progression of already-transformed cells through secretion of inflammatory mediators. We investigated here whether the senescent fibroblast secretome might have an impact on the very first stages of carcinogenesis. We chose the cultured normal primary human epidermal keratinocyte model, because af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 76 publications
2
62
0
3
Order By: Relevance
“…In a mouse model of cutaneous SCC, cancer-associated fibroblasts induce SASP-like inflammation, angiogenesis, and tumor growth through an NF-κB-mediated mechanism, reinforcing the links between the SASP and tumorigenesis in the skin (Erez et al, 2010). Consistent with these findings and a role for the SASP in skin carcinogenesis, inhibition of MMPs can prevent skin cancer invasion (Malaquin et al, 2013; Woenne et al, 2010). And finally, very recent work by Kaur et al (2016) found that aged fibroblasts in the melanoma tumor microenvironment can secrete a Wnt antagonist, sFRP2, that can drive angiogenesis, metastasis, and resistance to targeted therapies such as vemurafenib.…”
Section: Introductionmentioning
confidence: 73%
“…In a mouse model of cutaneous SCC, cancer-associated fibroblasts induce SASP-like inflammation, angiogenesis, and tumor growth through an NF-κB-mediated mechanism, reinforcing the links between the SASP and tumorigenesis in the skin (Erez et al, 2010). Consistent with these findings and a role for the SASP in skin carcinogenesis, inhibition of MMPs can prevent skin cancer invasion (Malaquin et al, 2013; Woenne et al, 2010). And finally, very recent work by Kaur et al (2016) found that aged fibroblasts in the melanoma tumor microenvironment can secrete a Wnt antagonist, sFRP2, that can drive angiogenesis, metastasis, and resistance to targeted therapies such as vemurafenib.…”
Section: Introductionmentioning
confidence: 73%
“…PAR 1 upregulation may be explained by the higher mean age of the diabetic patients compared to the systemically healthy patients, as there is a growing body of evidence indicating that changes in the transcriptional and post‐transcriptional regulation are associated with aging. In fact, a recent study by Malaquin et al ., have shown that aging is associated with an increased expression of PAR 1 in the skin . This result may also be explained by the fact that AGEs in diabetics increase the production of thrombin , which may trigger the thrombin–PAR 1 axis with an ultimate enhancement of PAR 1 expression .…”
Section: Discussionmentioning
confidence: 98%
“…Persistent DNA damage and DDR signaling triggers senescent cells to secrete immunomodulatory proteins, a phenomenon known as the senescence-associated secretory phenotype (SASP) (Campisi and d'Adda di Fagagna, 2007; Fumagalli and d'Adda di Fagagna, 2009). SASP factors range from inflammatory and immune-modulatory cytokines to chemokines as well as growth factors, shed cell surface molecules, survival factors and extracellular matrix remodeling enzymes (Coppé et al, 2008; Ohanna et al, 2011; Acosta et al, 2013; Malaquin et al, 2013). Together, they impinge on cell-fate decisions in neighboring cells or the tissue microenvironment.…”
Section: Dna Damage-driven Inflammation and Diseasementioning
confidence: 99%